1992
DOI: 10.1007/bf00203251
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of acid invertase and comparison with acid phosphatase in the ericoid mycorrhizal fungus Hymenoscyphus ericae (Read) Korf and Kernan

Abstract: Fractions of acid invertase and acid phosphatase of the ericoid mycorrhizal fungus Hymenoscyphus ericae (Read) Korf & Kernan were compared by column chromatography and polyacrylamide gel electrophoresis. Acid invertase levels were measured during the exponential phase after 14 days growth in pure culture. Most acid invertase was wall associated (50%) with 41% forming an extracellular fraction and 9% a soluble, cytoplasmic fraction. The wall-bound fraction was partially solubilized by 1 M NaC1, bulked with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Although some fungi possess cell wall‐bound invertase and transporters for Suc uptake (Aked & Hall, 1993; Lam et al ., 1994), this is not confirmed in AM fungi. In ericoid mycorrhizal fungus Hymenoscyphus ericae (Read) Korf & KernanMost, 50% of an acid invertase is wall‐associated, 41% forming an extracellular fraction and 9% a soluble, cytoplasmic fraction (Straker et al. , 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some fungi possess cell wall‐bound invertase and transporters for Suc uptake (Aked & Hall, 1993; Lam et al ., 1994), this is not confirmed in AM fungi. In ericoid mycorrhizal fungus Hymenoscyphus ericae (Read) Korf & KernanMost, 50% of an acid invertase is wall‐associated, 41% forming an extracellular fraction and 9% a soluble, cytoplasmic fraction (Straker et al. , 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Although some fungi possess cell wall-bound invertase and transporters for Suc uptake (Aked & Hall, 1993;Lam et al, 1994), this is not confirmed in AM fungi. In ericoid mycorrhizal fungus Hymenoscyphus ericae (Read) Korf & KernanMost, 50% of an acid invertase is wall-associated, 41% forming an extracellular fraction and 9% a soluble, cytoplasmic fraction (Straker et al, 1992). Studies on the detection of invertase activity, sugar uptake and isolation of the genes codifying sugar transporters in the AM germ tubes will eliminate the credence of sucrose uptake in AM fungal cells during the presymbiosis.…”
Section: Effects Of Phosphate and Sucrose On Hyphal Growth And H + Flmentioning
confidence: 99%
“…Pyrenopeziza brassicae, Walters et al, 1996, Sporisorium reilianum, Bhaskaran andSmith, 1993, Uromyces fabae, Voegele et al, 2001) but also ericoid mycorrhizal fungi (e.g. Hymenoscyphus ericae, Straker et al, 1992;Hughes and Mitchell, 1996). Since it makes the fungus dependent on the plant partner, lack of invertase might partially explain the low plant defense response faced by ectomycorrhizal fungi compared to pathogenic interactions (Smith and Read, 1997).…”
Section: Fungal Carbohydrate Support In Symbiosismentioning
confidence: 95%
“…It is commonly accepted that sucrose, which is excreted by plant root cells into the common apoplast of the plantfungus interface, is hydrolysed by a plant-derived invertase in EM symbiosis (Lewis and Harley, 1965a;Salzer and Hager, 1991;Rieger et al, 1992;Schaeffer et al, 1995;Nehls, 2004). The lack of an invertase in (at least many) EM fungi (Palmer and Hacskaylo, 1970;Salzer and Hager, 1991;Hatakeyama and Ohmasa, 2004;Daza et al, 2006) is a profound difference from phytopathogenic (Walters et al, 1996;Voegele et al, 2001) and also ericoid mycorrhizal fungi (Straker et al, 1992;Hughes and Mitchell, 1996). In combination with their low cell wall-degrading activity (compared with wood-and litter-degrading but also ericoid mycorrhizal fungi), lack of invertase activity makes EM fungi dependent on the activity of the plant partner (Smith and Read, 1997), which might be essential for the function of this type of symbiosis.…”
Section: Fungal Carbohydrate Nutrition In Symbiosismentioning
confidence: 99%